2013
DOI: 10.1556/avet.2012.061
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of GDF9, TGFB1, TGFB2 and TGFB3 in porcine oocytes isolated from follicles of different size before and after culture in vitro

Abstract: The TGFB superfamily genes are involved in several important cell functions, including proliferation and differentiation, and the role of the expression of these genes in growth and development of theca and granulosa cells is well recognised. However, the dependence between the stage of oocyte maturation or follicular size and the expression of these genes in pigs is still not entirely known. This study was aimed at investigating the expression pattern of GDF9, TGFB1, TGFB2 and TGFB3 in porcine oocytes before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Our recent study focused on the expression analysis of TGFB genes including TGFB1, TGFB2, TGFB3, and GDF9 in porcine oocytes before and after in vitro maturation (IVM), as well as in gametes collected from follicles of various sizes (16). We found an increased expression of TGFB1 and TGFB2 in oocytes isolated from larger size follicles compared to medium and small ones, whereas TGFB3 and GDF9 expression was unchanged.…”
Section: Resultsmentioning
confidence: 98%
“…Our recent study focused on the expression analysis of TGFB genes including TGFB1, TGFB2, TGFB3, and GDF9 in porcine oocytes before and after in vitro maturation (IVM), as well as in gametes collected from follicles of various sizes (16). We found an increased expression of TGFB1 and TGFB2 in oocytes isolated from larger size follicles compared to medium and small ones, whereas TGFB3 and GDF9 expression was unchanged.…”
Section: Resultsmentioning
confidence: 98%
“…Genes belonging to TGFB superfamily are important regulators; they are called also “checkpoints of oocyte maturation potential" [23]. INHA and INHB are members of TGFB superfamily and it is suggested that they regulate important stages of oocyte maturation in vivo and in vitro [2426].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression studies using mice and rats showed that TGFB3 are involved in reproductive functions, such as gonadal and secondary sex organ [42][43][44][45]. In swine, the TGFB gene superfamily, which includes TGFB3, has been identified to be expressed in ovarian follicles of different sizes before and after in vitro culture in porcine oocytes collected from crossbred Landrace gilts at 155 days of age [46]. This study suggested that the TGFB gene superfamily is associated with the stage of maturation of porcine oocytes and the follicle size [46].…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
“…In swine, the TGFB gene superfamily, which includes TGFB3, has been identified to be expressed in ovarian follicles of different sizes before and after in vitro culture in porcine oocytes collected from crossbred Landrace gilts at 155 days of age [46]. This study suggested that the TGFB gene superfamily is associated with the stage of maturation of porcine oocytes and the follicle size [46]. With regards to IRF2BPL, this gene encodes for a transcription factor that regulates neuronal networks controlling female reproductive function in nonhuman primates and rodents [47].…”
Section: Genome-wide Association Analysismentioning
confidence: 99%